Sistem Informasi Geografis Jalur Transportasi Angkutan Umum Berbasis Web: Studi Kasus Terminal Mardika Kota Ambon - Titasari Rahmawati; Timothy John Pattiasina; Michael Samuel Syaranamual (KONSTELASI: Konvergensi Teknologi dan Sistem Informasi, 2022)
Public transportation in Ambon city is very helpful in supporting people's daily activities, So, in this final project, the author develops an information system for Ambon city transportation routes, a website that can helping Mardika terminal workers to managing public transportation data and routes of public transportation at the Mardika terminal in Ambon city. And for people in the city of Ambon can get information about public transportation routes, especially at the Mardika terminal, in Ambon city. This system using the throw-away prototyping software development method, and also this system using the black box testing method, this method tested by Mardika terminal workers, and then proceed with user acceptance testing. by providing an inquiry form to terminal workers and passengers. And the result is that this system can provide information in the form of public transport prices, schedules, and public transport routes, this system, it can help passengers and can assist Mardika terminal workers in managing active public transportation routes in Ambon City.